2019
DOI: 10.1038/s41598-019-41709-w
|View full text |Cite
|
Sign up to set email alerts
|

Multiple ionization state of Arq+ ions during collisions near the Bohr velocity

Abstract: In order to clarify the mechanism and the influence of the initial charge state and target atomic parameters for the formation of L-shell multiple ionization state of Ar q+ ions produced by the collisions near the Bohr velocity, the k-shell x-ray emission of Ar is measured for 1.2 MeV Ar q+(q=4, 6, 8, 9, 11, 12) ions impacting on V target and 3 MeV Ar 11+ ions interacting with selected targets (Z 2 = 23, 26, 27, 28, 29,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…5 and 6 in Ref. [44], it was found that the x-ray energy of Ar K α and K β and the relative intensity ratio of K β to K α are all dwindled along with the target atomic number. This means that the multiple-ionization degree of Lshell decreases with the increase of target atomic number.…”
Section: X-ray From the Projectilementioning
confidence: 95%
See 1 more Smart Citation
“…5 and 6 in Ref. [44], it was found that the x-ray energy of Ar K α and K β and the relative intensity ratio of K β to K α are all dwindled along with the target atomic number. This means that the multiple-ionization degree of Lshell decreases with the increase of target atomic number.…”
Section: X-ray From the Projectilementioning
confidence: 95%
“…Although the Ar L-shell x-rays were not observed in the present work, the ionization of L-shell electrons can be deduced from the K-shell x-ray emission. In the previous work, [44] we investigated the characteristic of Ar K-shell xray. As shown in Figs.…”
Section: X-ray From the Projectilementioning
confidence: 99%
“…The number of incident ions on the target was monitored temperally with a calibrated transmitting Faraday cup. More experimental details can be found in Zhou et al (2019).…”
mentioning
confidence: 99%